Utilization of Prevention of Mother-to-Child Transmission of HIV Services and Associated Factors among Antenatal Care Attending Mothers in Sebeta Town, Central Ethiopia - Hailu Merga; Kifle Woldemichael; Lamessa Dube (Hindawi Limited, 2016)
Background. HIV transmission from mother to child continues to be the major source of HIV infection among children under the age of fifteen. Targeting pregnant women attending antenatal clinics provides a unique opportunity for implementing prevention of mother-to-child transmission (PMTCT) programs against HIV infection of newborn babies. This study assessed utilization of PMTCT service of HIV and associated factors among ANC attending mothers. Methods. An institutional based cross-sectional study was conducted from February 20 to March 30, 2015, using exit interviews with 377 ANC attendees using consecutive sampling method. In-depth interviews with service provider were conducted to complement the quantitative data. Data were entered and analysed using EpiData and SPSS, respectively. Results. The prevalence of PMTCT service utilization was 86.9% in this study. Only 8.6% of respondents attended the facility for HCT. After controlling confounders using logistic regression, PMTCT service utilization was associated with age (25-34) of respondents (AOR (95% CI) = 0.46 (0.22, 0.97)), mother's occupational status (being merchant AOR (95% CI) = 0.31 (0.12, 0.83), government employee AOR (95% CI) = 0.05 (0.01, 0.28), student AOR (95% CI) = 0.1 (0.01, 0.44), and daily laborer AOR (95% CI) = 0.13 (0.05, 0.33)), husband's educational status (lack of formal education (AOR (95% CI) = 3.3 (1.1, 9.9))), having discussion with husband (AOR (95% CI) = 6.1 (2.6, 14.1)), partner tested (AOR (95% CI) = 8.2 (1.9, 34.46)), and being not satisfied with the service (AOR (95% CI) = 0.46 (0.2, 0.99)). Conclusions. This study revealed that utilization of HIV counseling and testing during antenatal care was high among pregnant women in Sebeta town. It highlights that focusing on improvement of quality and coverage of health services has significant effects on PMTCT service utilization. Effective use or uptake of ARV drug among HIV-positive pregnant women should be further investigated so that utilization will be enhanced.